Probiotic Intervention for Oxidative Stress in Undernutrition - BALQIS, GASELA ZALIANTI; BERAWI, KHAIRUN NISA; RATNA, MAYA GANDA; SUTYARSO (Fakultas Kedokteran Universitas Lampung, 2025)
Undernutrition is a critical global health challenge, creating impaired physiological function and heightened oxidative stress. This elevated oxidative stress state is driven by deficient antioxidant intake and increased production of reactive oxygen species (ROS), which can exacerbate tissue damage and nutritional status. Additionally, the gut microbiota has been identified as a crucial regulator of systemic metabolic and inflammatory health. Probiotics, as modulators of this microbiome, have emerged as a potential therapy. This narrative review aims to summarize and discuss the current evidence linking probiotic intervention to the mitigation of oxidative stress in conditions of undernutrition. The exploration of proposed biological mechanisms includes the enhancement of endogenous antioxidant enzymes (like SOD and GPx), the reduction of lipid peroxidation markers (such as MDA), and the strengthening of the intestinal barrier. The existing literature indicates the potential of specific strains, particularly Lactobacillus and Bifidobacterium, in reducing oxidative damage through the modulation of inflammatory pathways and the production of antioxidant metabolites. In conclusion, probiotics are feasible as a low-cost adjuvant (supportive) therapy for managing the complex pathophysiology of undernutrition, although the establishment of standard protocols still requires further clinical validation.